PLIVANJE KAO DIO OPŠTE DRUŠTVENE KINEZIOLOŠKE AKTIVNOSTI - Drago Milošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Apart form the fact that the swimming is one of the basic sports, it is not in the suitable way presented through the school program, through the programs for the recreation, sport and kin therapy in Montenegro. The swimming, in its essence unites the different elements and levels of "game skillness" (homo ludens) and competitive spirit. The swimming demonstrated from the game and pleasure level, including the different levels of the competition, reaches the professional sport quality. Nowadays, the swimming is recognized as a very popular sport. So the author asks himself: "What is the reason for its popularity, and why the swimming has become the suitable medium of the social involvement and engagement? With which specific features, facilities and structural movements the swimming attracts, justifies and occupies the numerous numbers of people from the different social, cultural and age categories? Author tries to answer the questions by using the analytic definitions of the anthropology and kinesiology swimming summary. Analyzing the underlined problem, author concludes that the swimming as very important form of the social engagement must be researched in the interdisciplinary way. The existence of the swimming by itself on the brooklets, rapids, lakes, the sea or on the intended for the specific purpose swimming objects, the swimming practice for " the game and the pleasure", including the possibility to satisfy the different purposes, followed by already "agreed" and the official rules, from the irrational and spontaneous to the agonal one where everything happens according to "the rules", induced the author to process the mentioned problem in the following analytic way: 1. Swimming analysis as the movement activity 2. Swimming suitable for the game and competition. 3. Sociology - psychological analysis of the swimming motive relations. 4. Swimming interdisciplinary nature as the sociable and sport activity. 5. The position and role of the swimming in the swimming (and sport) organizations. Keywords